2009
DOI: 10.1002/adma.200900480
|View full text |Cite|
|
Sign up to set email alerts
|

Macroscopic Single‐Walled‐Carbon‐Nanotube Fiber Self‐Assembled by Dip‐Coating Method

Abstract: Pure macroscopic single-walled-carbon-nanotube (SWNT) fibers are fabricated by using a dip-coating method without any additive or additional electrical equipment or complex apparatus. The present method only utilizes microfluidics, which includes capillary condensation, capillary flow, and surface tension, and results in the self-assembly and self-alignment of SWNT colloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…The improved mechanical and electrical properties of above aligned nanotube/polymer composite have been realized through the direct use of nanotube arrays, sheets, and fibers. In the case of other approaches to align nanotubes (Baji et al, 2010;Ge et al, 2004;Go et al, www.intechopen.com 2004; Haggenmueller et al, 2003;Jang et al, 2009;Ji et al, 2009;Kang et al, 2009;Razal et al, 2007;Vigolo et al, 2000Vigolo et al, , 2002, similar improvements were also observed. For instance, aligned nanotube/polyacrylonitrile fibers after hot-stretching treatment showed a significant enhancement of tensile strength by 320.7% (Ji et al, 2009), while aligned nanotube/epoxy arrays induced by electric field could improve electrical conductivities by four orders of magnitude in the direction of alignment .…”
Section: Preparation Of Aligned Carbon Nanotube/polymer Compositessupporting
confidence: 59%
See 1 more Smart Citation
“…The improved mechanical and electrical properties of above aligned nanotube/polymer composite have been realized through the direct use of nanotube arrays, sheets, and fibers. In the case of other approaches to align nanotubes (Baji et al, 2010;Ge et al, 2004;Go et al, www.intechopen.com 2004; Haggenmueller et al, 2003;Jang et al, 2009;Ji et al, 2009;Kang et al, 2009;Razal et al, 2007;Vigolo et al, 2000Vigolo et al, , 2002, similar improvements were also observed. For instance, aligned nanotube/polyacrylonitrile fibers after hot-stretching treatment showed a significant enhancement of tensile strength by 320.7% (Ji et al, 2009), while aligned nanotube/epoxy arrays induced by electric field could improve electrical conductivities by four orders of magnitude in the direction of alignment .…”
Section: Preparation Of Aligned Carbon Nanotube/polymer Compositessupporting
confidence: 59%
“…The surface tension, jet elongation, and slow relaxation of nanotubes contribute to orientation of nanotubes. Some other approaches including coagulation-based spinning (Razal et al, 2007;Vigolo et al, 2000Vigolo et al, & 2002, melting spinning (Haggenmueller et al, 2003), dip coating method through microfluidic phenomena (Jang et al, 2009), and orientation by external stimuli such as mechanical interaction (Ji et al, 2009) had been also developed to synthesize aligned nanotube/polymer fibers. However, similar to the composite arrays and films, the nanotube alignments in the resulting composite fibers are much lower compared to the direct use of pure nanotube fibers.…”
Section: Preparation Of Aligned Carbon Nanotube/polymer Compositesmentioning
confidence: 99%
“…To deposit CNTs on the flexible substrates, various methods have been developed, including spray coating, dip coating, bar coating, and inkjet printing [18,19]. Among them, the spray coating method has the advantage that the thickness of deposited CNTs can be controlled precisely.…”
Section: Solution-based Deposition Of Cntsmentioning
confidence: 99%
“…Various macroscopic forms of CNTs have been produced, including fibers, yarns, films, sheets and foams [13][14][15][16][17][18]. Each structure shows a unique geometry and functionality depending on the manner in which CNTs are assembled [19,20].…”
Section: Introductionmentioning
confidence: 99%